# Please look at the attached file! Thank you

### 1 Answer | Add Yours

If the frequency f varies directly with the square root of the tension T and inversely with the length L, it could be expressed by the formula

`f = ksqrt(T)/L` , where k is the proportionality constant, a number independent on T and L.

If the length is doubled, it will become 2L, and if the tension is quadrupled, it will become 4T. The constant k will remain the same, as it does not depend on L and T.

The new frequency, F, will then become

`F = k sqrt(4T)/(2L)`

The square root of 4T can be simplified as follows:

`sqrt(4T) = sqrt(4)* sqrt(T) = 2sqrt(T)`

Plugging this into the expression for F above, we get

`F = k (2sqrt(T))/(2L) = k sqrt(T)/L`

Comparing the final result with the original formula for frequency f, we see that they are the same. So, F = f, which means that

**the frequency will not change if the tension is quadrupled and the length is doubled.**